2010
DOI: 10.1051/0004-6361/201014097
|View full text |Cite
|
Sign up to set email alerts
|

Planetary detection limits taking into account stellar noise

Abstract: Context. Stellar noise produced by oscillations, granulation phenomena (granulation, mesogranulation, and supergranulation), and activity affects radial velocity measurements. The signature of the corresponding effect in radial velocity is small, around the meterper-second, but already too large for the detection of Earth-mass planets in habitable zones. Aims. We address the important role played by observational strategies in averaging out the radial velocity signature of stellar noise. We also derive the pla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
311
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 284 publications
(323 citation statements)
references
References 47 publications
11
311
1
Order By: Relevance
“…This difference may be caused by the fact that HD 219828 is an early-G star, slightly evolved beyond the main sequence. It is indeed well known that stars of earlier type and more evolved stars present higher granulation noise in radial velocities (see Dumusque et al 2011, and references therein). It is also known that stellar activity can produce signals that can mimic planetary companions at different timescales (e.g.…”
Section: Radial-velocity Fittingmentioning
confidence: 92%
“…This difference may be caused by the fact that HD 219828 is an early-G star, slightly evolved beyond the main sequence. It is indeed well known that stars of earlier type and more evolved stars present higher granulation noise in radial velocities (see Dumusque et al 2011, and references therein). It is also known that stellar activity can produce signals that can mimic planetary companions at different timescales (e.g.…”
Section: Radial-velocity Fittingmentioning
confidence: 92%
“…From the study by Dumusque et al (2011b) we have learned that stellar pulsations are best averaged out by extending the measurement over a time longer than the typical stellar oscillation period. Because our targets are mainly bright G and K dwarfs, we ended up with exposure times of typically 15 minutes.…”
Section: Observational Strategymentioning
confidence: 99%
“…For most stars, integrations of 15 minutes are sufficient. - Dumusque et al (2011a) have shown that stellar granulation in solar-type stars can induce radial velocity variability comparable to or larger than 1 m s −1 on longer timescales compared to acoustic modes. Several measurements spanning several hours are requested to damp the granulation noise.…”
Section: The Harps Program To Search For Very Low Mass Planetsmentioning
confidence: 99%